2017
DOI: 10.4103/sja.sja_625_16
|View full text |Cite
|
Sign up to set email alerts
|

Use of rocuronium and sugammadex under neuromuscular transmission monitoring in a patient with multiple sclerosis

Abstract: Multiple sclerosis (MS) is a potentially disabling disease characterized by demyelinating lesions in the central nervous system. One of the anesthetic challenges encountered in surgical patients with MS is the management of neuromuscular blockade (NMB) and its reversal. We report a case of a 31-year-old female patient suffering from MS, who underwent gynecological surgery under general anesthesia with sevoflurane, fentanyl, and rocuronium which was successfully reversed with sugammadex. Neuromuscular transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It is reported that general anesthesia and surgical stress may cause exacerbation of MS as well as cases in which no attack is observed in postoperative follow-up. 3,5,6 One of the points to be considered in MS patients is to maintain the body temperature in a stable manner. It is known that the increase in the body temperature causes transmission block in demyelinated axons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that general anesthesia and surgical stress may cause exacerbation of MS as well as cases in which no attack is observed in postoperative follow-up. 3,5,6 One of the points to be considered in MS patients is to maintain the body temperature in a stable manner. It is known that the increase in the body temperature causes transmission block in demyelinated axons.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of full recovery of muscular strength may cause a big problem in these patients. 3 Hence, the anesthesiologist must choose the most suitable and the most secure method for the patient. Sugammadex, with a gammacyclodextrin structure, is a selective agent which encapsulates relaxant mus-Turkiye Klinikleri J Anest Reanim 2018;16(2):63-6 63 Gamze TALİH, a…”
mentioning
confidence: 99%
“…The reports on multiple sclerosis patients did not suggest an altered dose of rocuronium or unusual response to sugammadex. However, a resistance to rocuronium was described by Staikou et al manifesting as delay in onset of action following 1 mg/kg of rocuronium [55]. Transverse myelitis involves myelin destruction due to spinal cord inflammation.…”
Section: Neuropathies (Table 4)mentioning
confidence: 99%
“…Sugammadex forms a complex with the neuromuscular blocking agents rocuronium or vecuronium in plasma and thereby reduces the amount of neuromuscular blocking agent available to bind to nicotinic receptors in the neuromuscular junction. The release of receptors encourages muscle movement [9,10]. The molecular encapsulation process occurs at a ratio of 1:1, and after when sugammadex is intravenously injected, it is bonding with neuromuscular agents and reducing their concentration in plasma [3,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical studies of neuromuscular blocking drugs; documented that incomplete recovery is associated with various side effects such as muscle weakness, airway obstruction, and respiratory complications [14,15]. Sugammadex provides a new treatment option to reverse the effects of those medications and possibly help patients quicker recovery and minimal side effects sooner post-surgery [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%